Time and the Reader of the Roman de la Rose. (2nd April 2020) - Victor, Jacqueline
ABSTRACT: This article argues for reading the Roman de la Rose according to an asynchronous model of narrative time. In particular, this article shows that the Roman de la Rose explicitly thematizes and inscribes its reader within a non-linear praxis of reading that has consequences for how meaning is forged within vernacular verse narrative. It begins by establishing a view of narrative time, and the reader's affective experience of time, according to an Augustinian model that allows for asynchronous experience to pass through a present moment of reading. The article then outlines the temporal orientations of Guillaume de Lorris's and Jean de Meun's poems, which it views as presenting distinct modes of reading the Roman de la Rose according to the dual functions of anticipation and memory.